PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) PADA BERBAGAI DOSIS PUPUK ORGANIK DAN INTENSITAS PENGOLAHAN TANAH ULTISOLS BANTEN - Dewi Firnia; Andi Apriany Fatmawaty (Jurnal Agroekoteknologi, 2009)
ABSTRACT This Research aim to to know sweet maize crop result and growth ( Zea Mays Saccharata Sturt.) At various organic manure dose and intensity processing of soil tillage,This research have been executed in kampong baru petir Banten. Research take place from June until September 2008. Research use Random Device of Group ( factorial RAK) Pattern, consisting of two factor and three restating, first factor is organic manure dose with four level that is, 0; 10; 20; and 30 ha-1 ton. Second factor is intensity processing of soil tillage with three level that is, once, twice, and thrice processing of soil tillage, so that there are 12 treatment combination and 36 set of attempt. Result of research indicate that organic manure dose differ reality, clean weighing of cob at organic manure dose 10 ha-1 ton equal to 1.386,8 g per check, organic manure dose 20 ha-1 ton equal to 1.316,27 g per organic manure and check 30 ha-1 ton equal to 1.393,83 g per check. Intensity Processing of soil tillage show to differ is not real and also  not happened interaction among organic manure dose with intensity processing of soil tillage.Key words: soil tillage, organic manure, Ultisols